THE PLACE OF STRATEGY IN AN CRISIS MANAGEMENT SYSTEM OF ENTERPRISES - YEPIFANOVA, Iryna; BOLOTNOV, Denis (Herald of Khmelnytskyi National University. Economic sciences, 2022)
In the conditions of russia's armed aggression, the loss of a significant number of enterprises of their production capacities, the deterioration of the logistics supply system, the instability of the national currency exchange rate requires active anti-crisis management from all enterprises, which must be carried out in accordance with the formed enterprise development strategy. Despite a significant amount of research in the direction of anti-crisis management, the issue of the relationship between anti-crisis and strategic management requires further research.The purpose of the article is to determine the relationship and place of strategy in the anti-crisis management system in modern conditions.The article systematizes approaches to determining the essence of the strategy and its place in the anti-crisis management system. It was determined that in modern conditions, the implementation of an anti-crisis management strategy is important for all enterprises, regardless of the form of management. The basic strategies of enterprise development are summarized: strategies of concentrated growth, strategies of integrated growth, strategies of diversified growth, strategies of reduction.The stages of the development of a crisis situation at the enterprise are summarized: the appearance of signs of a crisis; crisis detection; financial response to the unfolding of the crisis; unfolding (deepening) of the crisis; the company's reaction to the crisis. The anti-crisis management strategy is defined as an interrelated sequence of actions to ensure the effective economic activity of the enterprise under the conditions of limited resources and the influence of crisis factors. The anti-crisis management strategy should consist of a strategy for overcoming crisis phenomena and a strategy for preventing crisis phenomena. Both components are important and require constant monitoring of the external and internal environment of the enterprise. The stages of the implementation of the anti-crisis strategy of the enterprise are determined.
Keywords: strategy; strategic management; anti-crisis management